OVERCOMING LITERACY BARRIERS: AN ANALYSIS OF READING AND WRITING DIFFICULTIES IN PRIMARY SCHOOL - Supriya Garg; Dr.Usha Baxi (Revista Electronica de Veterinaria, 2024)
This study investigates the factors influencing the development of reading and writing skills in children, comparing teaching methodologies in Montessori and government schools. The research identifies environmental, neurological, and socio-demographic influences as significant contributors to literacy challenges. Data reveal that Montessori schools consistently outperform government schools in fostering reading fluency, comprehension accuracy, and writing proficiency due to their student-centered teaching strategies. Key findings indicate that Montessori schools demonstrate higher effectiveness in employing phonics-based approaches, storytelling, and the use of visual aids, with growth rates in reading fluency (15% vs. 8%), comprehension accuracy (12% vs. 7%), and writing accuracy (10% vs. 5%). Conversely, government schools face systemic challenges, including resource limitations, large class sizes, and insufficient individualized attention. The study underscores the importance of early detection of literacy difficulties and tailored interventions to support struggling learners. Strategies such as breaking tasks into manageable steps, providing additional time, and fostering inclusive learning environments are shown to enhance student outcomes. Collaborative efforts involving teachers, parents, and specialists are essential to address the diverse needs of learners effectively. Recommendations emphasize the integration of affordable diagnostic tools, teacher training, and resource rooms to ensure equitable access to quality education. This research highlights the critical need for systemic improvements in government schools and the potential benefits of adopting Montessori-inspired practices for holistic literacy development.